2022
DOI: 10.3390/jof8060602
|View full text |Cite
|
Sign up to set email alerts
|

Host–Pathogen Interactions between Metarhizium spp. and Locusts

Abstract: The progress in research on the interactions between Metarhizium spp. and locusts has improved our understanding of the interactions between fungal infection and host immunity. A general network of immune responses has been constructed, and the pathways regulating fungal pathogenicity have also been explored in depth. However, there have been no systematic surveys of interaction between Metarhizium spp. and locusts. The pathogenesis of Metarhizium comprises conidial attachment, germination, appressorial format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 133 publications
(216 reference statements)
0
11
0
Order By: Relevance
“…An intriguing finding in the current study is that EPF utilizes host immunity to minimize the competition of opportunistic bacteria in the hemolymph. When EPF germ tubes penetrate the integument and enter the hemocoel, they are exposed to the strong immune reactions of the insect host [ 46 , 47 ]. EPF usually employs two strategies to survive in the hemocoel: evading and suppressing the host immunity [ 6 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An intriguing finding in the current study is that EPF utilizes host immunity to minimize the competition of opportunistic bacteria in the hemolymph. When EPF germ tubes penetrate the integument and enter the hemocoel, they are exposed to the strong immune reactions of the insect host [ 46 , 47 ]. EPF usually employs two strategies to survive in the hemocoel: evading and suppressing the host immunity [ 6 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that ecdysone triggers the expression of many immune-related genes, such as PRRs and AMPs [ 42 , 63 ], an increased 20E titer upon M. rileyi infection may contribute to the upregulation of AMPs, either directly or indirectly. The humoral antibacterial response of H. armigera upon fungal infection may be coordinated by the Toll pathway and ecdysone, as shown in the locust [ 47 ]. Unlike the decreased 20E levels upon M. rileyi conidial injection [ 41 ], we found that M. rileyi blastospore injection elevated the 20E titers.…”
Section: Discussionmentioning
confidence: 99%
“…The fungal infection can lead to the death of the mosquito or disrupt its further development, such as eclosion, pupation, oviposition and reduced life span [13,25,[28][29][30][31]. EPF infection on adult mosquito has been extensively described, showing a similar phenomenon as other insects [27]. Similar as in adults, topical infection of larvae can destroy the host hemocytes after penetrating the cuticle [32].…”
Section: Invasion Through Mosquito Cuticlementioning
confidence: 93%
“…They then penetrate the host's cuticle through a combination of mechanical force from turgor pressure and enzymes produced by the appressoria. This penetration allows the fungi to destroy the insect immune system and proliferate inside the insect [25][26][27]. Infection through the cuticle is undoubtedly the main pathway for EPF to target eggs, pupae, and adult mosquitoes with piercing-sucking mouthparts.…”
Section: Invasion Through Mosquito Cuticlementioning
confidence: 99%
“…However, specialization of M. acridum to hosts within Orthoptera is considered to have led to specific patterns of genetic and pathogenic adaptation. For example, unlike generalist Metarhizium species, which typically kill hosts of many insect orders quickly via toxins, M. acridum causes a systemic infection of host tissues along with increased evasion of the host immune system, eliciting a more gradual killing of their orthopteran host (Kershaw et al, 1999; Li & Xia, 2022). In addition, M. acridum has been shown to be more tolerant to physical stressors than other Metarhizium species, such as to ultraviolet light from solar radiation (Brancini et al, 2019; Fernandes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%